The practice of office-based buprenorphine treatment of opioid dependence: is it associated with new patients entering into treatment? - Sullivan, Lynn E; Chawarski, Marek; O'Connor, Patrick G; Schottenfeld, Richard S; Fiellin, David A (Drug and alcohol dependence, 2005)
Office-based buprenorphine holds the promise of bringing patients who have never received pharmacotherapy into treatment. In a cross-sectional and longitudinal analysis, we compared patients entering a clinical trial of buprenorphine in a Primary Care Clinic (PCC) and those entering a local Opioid Treatment Program (OTP) and we compared the clinical characteristics and treatment outcomes of PCC patients with no history of methadone treatment (new-to-treatment) to those with prior methadone treatment. PCC subjects (N=96) were enrolled in a 26-week randomized clinical trial of office-based buprenorphine/naloxone provided in a PCC. OTP subjects (N=94) were enrolled in methadone maintenance during the same time period. PCC subjects compared with OTP subjects were more likely to be male (77% versus 55%, p<0.01), full-time employed (46% versus 15%, p<0.001), have no history of methadone treatment (46% versus 61%, p<0.05), have fewer years of opioid dependence (10 versus 15, p<0.001), and lower rates of injection drug use (IDU) (44% versus 60%, p=0.03). The new-to-treatment PCC subjects were younger (36 years versus 41 years, p=0.001), more likely to be white (77% versus 57%, p=0.04), had fewer years of opioid dependence (7 versus 14, p<0.001), were less likely to have a history of IDU (35% versus 54%, p=0.07), and had lower rates of hepatitis C (25% versus 61%, p=0.002) than subjects with prior methadone treatment. Abstinence and treatment retention were comparable in both groups. The results suggest that office-based treatment of opioid dependence is associated with new types of patients entering into treatment. Treatment outcomes with buprenorphine in a PCC do not vary based on history of prior methadone treatment.
Keywords: Adolescent; Adult; Aged; Buprenorphine; Cross-Sectional Studies; Female; Humans; Male; Mental Health Services; Middle Aged; Narcotic Antagonists; Office Visits; Opioid-Related Disorders; Physician's Practice Patterns